2003
DOI: 10.12968/bjon.2003.12.sup3.11434
|View full text |Cite
|
Sign up to set email alerts
|

Fungating wounds: informing practice through knowledge/theory

Abstract: The assessment and management of fungating wounds is a challenging situation which necessitates nurses using many skills. Literature is limited, especially relating to the psychological issues that arise for the patient and his/her family. As nurses, we must begin to address this by considering how our philosophy, knowledge and theory impact on and inform our practice. This article will critique and explore the different influences that affect our way of being and thinking in the world and how we can guide pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Comprehensive assessment is particularly important in the context of complex disorders, such as malignant wounds, which are unique in every presentation, always difficult to treat, often incorporate a variety of problems and are capable of impacting dramatically on the quality of life of the patient and those caring for them. 32,40,41,46 The assessment should be ongoing and incorporate all domains of the patient's illness experience (not just the wound), how they are coping with it and the ongoing impact on their own life and that of their family. It should include their nutritional status, ability to self-care, psychosocial issues (depression, body image, sexuality), past health history, current morbidities, allergies, social support, strengths and coping abilities, spiritual and cultural needs.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive assessment is particularly important in the context of complex disorders, such as malignant wounds, which are unique in every presentation, always difficult to treat, often incorporate a variety of problems and are capable of impacting dramatically on the quality of life of the patient and those caring for them. 32,40,41,46 The assessment should be ongoing and incorporate all domains of the patient's illness experience (not just the wound), how they are coping with it and the ongoing impact on their own life and that of their family. It should include their nutritional status, ability to self-care, psychosocial issues (depression, body image, sexuality), past health history, current morbidities, allergies, social support, strengths and coping abilities, spiritual and cultural needs.…”
Section: Assessmentmentioning
confidence: 99%
“…47 The importance of comprehensive, individual assessments was highlighted by Laverty, who report-ed on long-held assumptions that had subsequently been proven false. 46 She discussed the tendency of some practitioners to assume they knew what patients were experiencing because they thought that every patient dealt with symptoms in the same way. As the author pointed out, we may know what is happening to a patient but we will not know how they perceive these experiences unless we take time to understand the meaning for each individual patient.…”
Section: Assessmentmentioning
confidence: 99%
“…Luka fungatings sulit disembuhkan karena sifatnya kanker (Naylor, 2002;Laverty, 2003). Terapi adjuvan, seperti terapi hormon, kemoterapi dan radioterapi dapat digunakan untuk memperlambat pertumbuhan kanker (Hallett, 1995), tetapi cenderung untuk memperpanjang dari waktu ke waktu dan ditandai oleh gejala malodour dan eksudat berat.…”
Section: Pendahuluanunclassified
“…The current dearth of information has been recognised by a number of authors who have highlighted the need for further research into the lived experience of malignant wounds so that it might be better understood (9–11). Schulz et al suggested that a greater understanding of the intensity and impact of malignant wounds upon the lives of patients would be an extremely valuable addition to existing literature (12).…”
Section: Background and Literature Reviewmentioning
confidence: 99%